2017
DOI: 10.1016/j.amjcard.2017.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Albuminuria With Cardiac Dysfunction in US Hispanics/Latinos

Abstract: Higher urine albumin-to-creatinine ratio (UACR) has been associated with cardiac dysfunction in the general population. We assessed the association of UACR with cardiac structure and function in the Echocardiographic Study of Latinos (Echo-SOL), an ancillary study of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) across 4 U.S. sites. Echo-SOL participants underwent standard 2-dimensional echocardiography, including speckle-tracking strain analysis. UACR was categorized as normal and high-norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Microalbuminuria is strongly associated with the morbidity and mortality of cardiovascular diseases in hypertensives, diabetics, and general population 1‐3 . Epidemiological data suggested that UACR levels are low in the general population, usually below the diagnostic criteria for microalbuminuria, 20 which was consistent with our data, only a small percentage of subjects were diagnosed with microalbuminuria (12.06%) or macroalbuminuria (1.49%). High‐normal albuminuria, which was below the diagnostic criteria for microalbuminuria, was reported to be capable of predicting the morbidity and mortality of cardiovascular diseases 7 , and UACR level was proved to be related with pulse wave velocity as well 13,14 .…”
Section: Discussionsupporting
confidence: 91%
“…Microalbuminuria is strongly associated with the morbidity and mortality of cardiovascular diseases in hypertensives, diabetics, and general population 1‐3 . Epidemiological data suggested that UACR levels are low in the general population, usually below the diagnostic criteria for microalbuminuria, 20 which was consistent with our data, only a small percentage of subjects were diagnosed with microalbuminuria (12.06%) or macroalbuminuria (1.49%). High‐normal albuminuria, which was below the diagnostic criteria for microalbuminuria, was reported to be capable of predicting the morbidity and mortality of cardiovascular diseases 7 , and UACR level was proved to be related with pulse wave velocity as well 13,14 .…”
Section: Discussionsupporting
confidence: 91%
“…There are conflicting findings with respect to the association between UACR and diastolic function. 13,14 The HyperGEN Study only found significant association between UACR and E/e′, 13 while Echo-SOL Study demonstrated significant associations of UACR with E/e and e′, respectively. 14 Our findings should be interpreted within the context of its strengths and limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies investigated the association of albuminuria with subclinical systolic and diastolic function in the general population 13,14 and in diabetic patients. 15 However, the findings regarding association of albuminuria with GLS were not consistent.…”
Section: Hfpefmentioning
confidence: 99%
See 1 more Smart Citation
“…Guglielmi MD et al 12 also had similar observation in their study and concluded that microalbuminuria was associated with significant changes in left ventricular morphology and more severe impairment of cardiac function. Hanna DB et al 13 in their study found that higher urine albumin-to-creatinine ratio (UACR) was associated with cardiac dysfunction in the general population.…”
Section: Discussionmentioning
confidence: 98%